Business management and sustainable development of coffee farming cooperatives in Peru: Cajamarca case - Montes Quispe, Lith (2022)
Cooperatives can be considered one of the key drivers of economic and social development in the world. Operating under a vision of solidarity, they have a socio-economic system where people voluntarily join to work together and obtain common benefits. However, their inadequate business management and corruption cases, in addition to the emblematic cases of crisis and the subsequent liquidation of emblematic cooperatives in Peru, have caused society to lose confidence in a model that aims to work for the welfare of the less fortunate. In this framework, the research aims to determine the influence of business management on the sustainable development of agricultural coffee cooperatives in the province of San Ignacio, department of Cajamarca in the 2017-2020 period. The methodology of the study was quantitative, bivariate, descriptive, cross-sectional, correlational, and applied. The instrument used was a questionnaire applied to 67 people, including directors, managers, and line managers of cooperatives. The results showed that the functions of planning, organization, staff integration, management, and control were key factors in achieving sustainable development in the coffee cooperatives for the period studied. It is concluded that the cooperative model is an instrument that enables the social, economic, and environmental development of the territories when it is professionally managed.